ISOLATION OF AnsB GENE FRAGMENT ENCODING L-ASPARAGINASE 2 ENZYME FROM Serratia plymuthica UBCF_13 AND IT’S IN-SILICO DOMAIN CHARACTERISTIC - Ananda, Abi Awfa Rahman; Nursyafi, Fauzan Syarif; Aliya, Lisana Shidiqqin; Hasibuan, Imron Martua; Alioes, Yustini; Endrinaldi , Endrinaldi; Adrial, Adrial; Elmatris , Elmatris; Jamsari, Jamsari; Lily Syukriani (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
Acute lymphoblastic leukemia(ALL) is one of the cancer diseases often occurs in children and causes high mortality in children. One of the chemotherapy treatment suggested is using L-Asparaginase 2. However due to its difficult production process making this approach expensive for the public. Therefore production technology of this enzyme is crucial enabling cheaper for ALL treatment. This study aimed to isolate the AnsB gene sequence from Serratia plymuthica UBCF_13 and perform its further in-silico analysis. The research was started by designing specific primers for the AnsB gene, isolating the AnsB gene fragment using PCR-based approach, sequencing the AnsB gene fragment, cloning the fragment to the plasmid vector and further transformed into E. coli DH5α cell. Further data analysis was carried out using some bioinformatics tools such as BLAST, MEGA X, I-TASSER InterPro. Sequence data result successfully verified that the full length of AnsB gene is 1047 bp. InterPro analysis indicated that the L-Asparaginase 2 from S. plymuthica UBCF_13 has 2 domains, namely L-Asparaginase N-terminal spanning from amino acid 26 to 216, while its C-terminal spanned from amino acid 235 to 345. The physical fragment of the gene was also successfully cloned to the pGEM-T Easy vector and subsequently transformed into E. coli DH5α cell. This result provided information for alternative sources of L-Asparaginase 2 and it’s possible engineering.